2017
DOI: 10.3748/wjg.v23.i15.2723
|View full text |Cite
|
Sign up to set email alerts
|

Optimal treatment for Siewert type II and III adenocarcinoma of the esophagogastric junction: A retrospective cohort study with long-term follow-up

Abstract: AIMTo determine the optimal treatment strategy for Siewert type II and III adenocarcinoma of the esophagogastric junction.METHODSWe retrospectively reviewed the medical records of 83 patients with Siewert type II and III adenocarcinoma of the esophagogastric junction and calculated both an index of estimated benefit from lymph node dissection for each lymph node (LN) station and a lymph node ratio (LNR: ratio of number of positive lymph nodes to the total number of dissected lymph nodes). We used Cox proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The most frequent metastatic lymph nodes are the proximal gastric lymph nodes, nodes at the esophageal hiatus, lower mediastinum and suprapancreatic lymph nodes. 33 Regarding this results and regarding the patterns of recurrence, many authors share the opinion that an extensive mediastinal lymph node dissection is unnecessary. 17 , 32 , 33 , 34 It therefore seems reasonable that the mediastinal lymphadenectomy via thoraco-abdominal approach is not mandatory.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The most frequent metastatic lymph nodes are the proximal gastric lymph nodes, nodes at the esophageal hiatus, lower mediastinum and suprapancreatic lymph nodes. 33 Regarding this results and regarding the patterns of recurrence, many authors share the opinion that an extensive mediastinal lymph node dissection is unnecessary. 17 , 32 , 33 , 34 It therefore seems reasonable that the mediastinal lymphadenectomy via thoraco-abdominal approach is not mandatory.…”
Section: Discussionmentioning
confidence: 87%
“…Many studies supported this approach for tumors types S II and S III. 17 , 23 , 32 , 33 , 34 Yamashita analyzed the pattern of lymph nodes involvement in patients of tumors extending in the region of the EGJ. They found that in gastric predominant EGJ tumors suprapancreatic lymph nodes had the highest metastases rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no standard proximal surgical margin exists for Siewert type II AEG. Hosoda et al [14] suggested that the lymph nodes of stations 1, 2, 3, and 7 can be dissected in Siewert type II and III AEG due to their high indexes of estimated benefit from lymph node dissection (IEBLDs). According to the report from Kurokawa et al [15], metastasis is associated with Siewert type II AEG ≥ 2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian countries, especially in China, most tumors in the esophagogastric junction are classified as Siewert type II and III, whereas in Western countries, type I is more prevalent . Surgical resection is still the main treatment option for patients with resectable AEG . For patients with Siewert type II AEG, because the tumor is located between the thoracic and abdominal cavities, cancer cells can metastasize to the abdominal or mediastinal lymph nodes through the lymphatic system.…”
Section: Introductionmentioning
confidence: 99%